Miniaturized Wavelength Interrogation For The Aircraft Structural Health Monitoring And Optofluidic Analysis - Guo, Honglei (Université d'Ottawa / University of Ottawa, 2014)
In this thesis, miniaturized wavelength interrogators based on planar lightwave circuits (PLCs) are investigated and developed for the optical fiber sensing applications in the aircraft structural health monitoring (SHM) and optofluidic analysis. Two interrogation systems based on an arrayed waveguide grating (AWG) and an Echelle diffractive grating (EDG) are developed and used to convert the optical sensing signals into strain, temperature, vibration, damage, and humidity information for the aircraft SHM. A fiber Bragg grating (FBG) sensing system using developed interrogators is then demonstrated in a field test for aircraft SHM applications. For optofluidic analysis, a PLCs based optofluidic device consisting of two on-chip lens sets is built to enhance the optical manipulation capability of particles. Then, a solution to a multi-functional Lab-on-a-Chip platform for optofluidic analysis is proposed, which integrates the developed particle maneuvering device, grating-structured sensors, and miniaturized interrogators.
Keywords: fiber optics; sensor; photonic integrated circuits; planar lightwave circuits; fiber Bragg grating; structural health monitoring; optoelectronics; optofluidics